Analysis of the Effect of Product, Price, Place and Promotion on Customer Satisfaction at BNI Taplus KCP Manado - Hidayat, Adrian; Tumbuan, Willem JFA; Soepeno, Djurwati (European Journal of Life Safety and Stability (2660-9630), 2021)
The purpose of this study was to determine the Analysis of the Effect of Product, Price, Place and Promotion on Customer Satisfaction at BNI Taplus KCP Manado. The location in this research is PT Bank BNI KCP Manado Jl. PiereTendean, SarioTumpaan. Wenang District, Manado City, North Sulawesi. As for the population in this study are all customers of PT. Bank BNI KCU Manado. The sampling method used Accidental Sampling, namely the determination of the sample based on chance, i.e. who happened to meet with the researcher can be used as a sample if deemed suitable by using the Slovin formula. So the number of samples in this study was 93 respondents. Research result. Product variables have a significant effect on customer satisfaction at BNI KCP Manado savings. The price variable has no significant effect on customer satisfaction at BNI KCP Manado savings. The place variable has a significant effect on customer satisfaction at BNI KCP Manado savings. Promotion variable has a significant effect on customer satisfaction at BNI KCP Manado savings.